"If he sees it with his own eyes, he will understand": how gender informed the content and delivery of a maternal nutrition intervention in Burkina Faso - Isler, Jasmin; Sawadogo, N. Hélène; Harling, Guy; Bärnighausen, Till; Adam, Maya; Sié, Ali; McMahon-Rössle, Shannon A. (Health policy and planning, 2020)
Abstract. A growing body of literature urges policymakers, practitioners and scientists to consider gender in the design and evaluation of health interventions
Advance access publication date: 27 February 202
Gesehen am 25.09.2020